2017
DOI: 10.1039/c7dt02255g
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxicity of strained Ru(ii) complexes: is it the metal complex or the dissociating ligand?

Abstract: A photochemically dissociating ligand in Ru(bpy)(dmphen)Cl [bpy = 2,2'-bipyridine; dmphen = 2,9-dimethyl-1,10-phenanthroline] was found to be more cytotoxic on the ML-2 Acute Myeloid Leukemia cell line than Ru(bpy)(HO) and prototypical cisplatin. Our findings illustrate the potential potency of diimine ligands in photoactivatable Ru(ii) complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…The half‐life (t 1/2 ) in water was found to be 4.3 min whereas it was 2.2 min in acetonitrile. As expected, t 1/2 in water was larger than in acetonitrile since the latter provides enhanced solvation of the photoproducts . However, it is important to note that the rate of photoejection is dependent on the concentration and volume of the solution as well as the incident power density.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The half‐life (t 1/2 ) in water was found to be 4.3 min whereas it was 2.2 min in acetonitrile. As expected, t 1/2 in water was larger than in acetonitrile since the latter provides enhanced solvation of the photoproducts . However, it is important to note that the rate of photoejection is dependent on the concentration and volume of the solution as well as the incident power density.…”
Section: Resultssupporting
confidence: 55%
“…Results of cell viability assays showed that the toxicity of dmphen was significantly higher than the aqua complex formed and thus proved that the Ru II center can act as a cage for the cytotoxic ligand. These findings uncovered the important role of the coordinating ligands in the biological activity of strained Ru II polypyridyl complexes . Similarly, another report by Bonnet and co‐workers illustrated that the photoreleased 6,6′‐dimethyl‐2,2′‐bipyridine (dmbipy) ligand is responsible for the phototoxicity of [Ru(bipy) 2 (dmbipy)] 2+ , whereas the Ru bis‐aqua photoproduct was found to be biologically inert .…”
Section: Introductionmentioning
confidence: 69%
“…46, 47 The cytotoxicity of the strained, ejecting ligands for compounds 1 and 4 , 2 and 5 , and 7 were tested, and no cytotoxicity was observed at concentrations up to 30 μM. Accordingly, the activity of the complexes was attributed to the biological interactions of the Ru(II) fragment.…”
Section: Resultsmentioning
confidence: 99%
“…However, we and others demonstrated recently that the second photoproduct obtained upon irradiation of [Ru(bpy) 2 (dmbpy)] 2+ in water, i.e. the free dmbpy ligand, is the actual cytotoxic species [8,9]. These findings resulted in the formulation of two questions: first, can we design a lightactivated ruthenium complex in which the ruthenium bis-aqua photoproduct is the sole cytotoxic species?…”
Section: Introductionmentioning
confidence: 99%